Diel patterns of predation and fledging at nests of four species of grassland songbirds. Issue 11 (1st May 2021) - Ribic, Christine A.; Rugg, David J.; Ellison, Kevin; Koper, Nicola; Pietz, Pamela J.
Abstract: Although it is common for nestlings to exhibit a strong bias for fledging in the morning, the mechanisms underlying this behavior are not well understood. Avoiding predation risk has been proposed as a likely mechanism by a number of researchers. We used video surveillance records from studies of grassland birds nesting in North Dakota, Minnesota, and Wisconsin to determine the diel pattern of nest predation and fledging patterns of four ground‐nesting obligate grassland passerines (Grasshopper Sparrow ( Ammodramus savannarum ), Savannah Sparrow ( Passerculus sandwichensis ), Bobolink ( Dolichonyx oryzivorus ), and Eastern Meadowlark ( Sturnella magna )). We used the nest predation pattern as a surrogate for predation activity to test whether nestlings minimized predation risk by avoiding fledging when predation activity was high and preferentially fledging when predation risk was low. Predation activity was significantly lower starting 3 hr before sunrise and ending 3 hr after sunrise, followed by a transition to a period of significantly higher activity lasting for 4 hr, before declining to an average activity level for the rest of the diel period. There was little evidence that the four grassland bird species avoided fledging during the high‐risk period and Savannah Sparrow fledged at higher rates during that period. All four species had hours during the low‐risk period where they fledged at higher rates, but only Grasshopper Sparrow fledged preferentially during that period. Bobolink and Eastern Meadowlark had multiple hours with high fledging rates throughout the daytime period, resulting in no relationship between probability of fledging and predation risk. Given the species variability in fledging pattern seen in our study, it is unlikely that there is a universal response to any driver that affects time of fledging. Further study is needed to understand the complex interplay between species ecology and drivers such as physiology, energetics, and predation in affecting grassland bird fledging behavior. Abstract : We investigated the predation activity pattern affecting four obligate grassland bird species and whether that affected the time of fledging. Nest predators had the lowest activity 3 hr before and after sunrise (blue bar) with their highest activity during mid‐morning to early afternoon (red bar). Overall, while the birds fledged significantly more during certain hours across the morning, there was little evidence that predation risk was a driver affecting the species' fledging patterns.